Vertebrate Faunal Remains from Grasshopper Pueblo, Arizona - Olsen, John W. (Book collections on Project MUSE., 1990)
Analyzes the bones of animals found at Arizona's 14th-century Grasshopper Pueblo in order to determine seasonality of procurement, the nature and underlying causes of hunter selectivity, and situational factors such as time constraints, task group size, and distance from the village.